Questioning the Assessment of Research Impact Illusions, Myths and Marginal Sectors - Thomas, Rhodri (Palgrave Critical University Studies,, 2018)
'This is quite simply a brilliant book, offering a critical analysis of impact and REF which is long overdue... It is a must-read for anyone seeking to understand how and why the growing need to show a particular kind of impact from research is restructuring academia; this new agenda has far reaching consequences for critical researchers, so-called marginal subjects and for everyday working cultures in academic departments.' -Professor Rosaleen Duffy, University of Sheffield, UK This book provides the first comprehensive assessment of non-academic research impact in relation to a marginal field of study, namely tourism studies. Informed by interviews with key informants, ethnographic reflections on the author's extensive work with trade and professional associations, and various secondary data, it paints a picture of inevitable research policy failure. This conclusion is justified by reference to ill-founded official conceptualisations of practitioner and organisational behaviour, and the orientation and quality of tourism research. The author calls for a more serious consideration of research-informed teaching as a means of creating knowledge flows from universities. Research with greater social and economic impact might then be achievable. This radical assessment will be of interest and value to policy makers, university research managers and tourism scholars. Rhodri Thomas is Professor of Tourism and Events Policy and Dean of the School of Events, Tourism and Hospitality Management, Leeds Beckett University, UK.